Insurgency Recruitment in Sadanga: Opportunities and the Effects of the Government Interventions - Fanao, Alban C.; Cawi, Robino D. (Eximia, 2023)
This study is about the insurgency recruitment in the municipality of Sadanga. The qualitative design, especially the narrative approach was used to determine the opportunities that provided the insurgents to recruit and the effects of anti-insurgency intervention programs to the insurgency recruitment in Municipality of Sadanga. Rebel returnees and elected officials in Sadanga were interviewed and from their responses, it was found that remoteness, territorial dilemma, poverty and family support are the factors seen by the rebels to recruit in the communities of Sadanga. However, with the government programs on anti-insurgency, release from threat, economic improvement and employment are seen as the effects of the intervention programs that restricted the insurgents to advance their recruitment in the municipality of Sadanga. The existing intervention program is providing the village employment and security assurance especially for the parents who are sending their children in school. They are no longer worried on the threat posed by this group recruiting their sons and daughters to join their organization. The study then recommends that the government will continue to bring development in remote places to eliminate reasons for residents to join in the left leaning group.